1974
DOI: 10.1002/1097-0142(197405)33:5<1411::aid-cncr2820330527>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Childhood non-Hodgkin's lymphoma— a study of 17 cases in Israel

Abstract: Seventeen children with non‐Hodgkin's lymphoma observed recently at the Chaim Sheba Medical Center are described. Two clinical forms of the disease are apparent: poorly‐differentiated lymphocytic lymphosarcoma presenting with mediastinal and peripheral nodal localization and occasional bone marrow infiltration, and Burkitt's lymphoma. In the tatter, predominantly affecting the Arab population, abdominal localization was, in most cases, the presenting symptom, with CNS and jaw involvement in some patients. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Pathological examination of the tumor revealed a malignant lymphoma resembling Burkitt's tumor. The clinical and histological characteristics of this " Burkitt-like " tumor occurring in Israeli children ( H u h et al, 1970;Sachs et al, 1973;Aghai et al, 1974) are indistinguishable from those of the so-called American Burkitt tumors (Dorfman, 1968;Carbone et al, 1969;Cohen et al, 1969) and similar childhood lymphomas in many European and Asian countries (Ahlstrom et al, 1967;Aramsri et al, 1967;Bound and Murray, 1967;Shanmugaratram et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Pathological examination of the tumor revealed a malignant lymphoma resembling Burkitt's tumor. The clinical and histological characteristics of this " Burkitt-like " tumor occurring in Israeli children ( H u h et al, 1970;Sachs et al, 1973;Aghai et al, 1974) are indistinguishable from those of the so-called American Burkitt tumors (Dorfman, 1968;Carbone et al, 1969;Cohen et al, 1969) and similar childhood lymphomas in many European and Asian countries (Ahlstrom et al, 1967;Aramsri et al, 1967;Bound and Murray, 1967;Shanmugaratram et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting that in Israel, Burkitt's lymphoma appears to affect the same ethnic groups. 2 The incidence of H.D. in Arab and Oriental Jewish children is definitely high, with a distinct histologic pattern, M.C.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed data on Arab cases living in Palestine have been published (Hulu et al, 1970;Aghai et al, 1974;Gotlieb-Stematsky et al, 1976;Goldblum et al, 1977;Buchner et al, 1978;Selzer 504 Y. LADJADJ et al et al, 1979a, b;Prokocimer et al, 1980), but no significant survival study could be found.…”
mentioning
confidence: 99%